Kesepadanan Penerjemahan Kosakata Bermuatan Budaya pada Anime Sen to Chihiro no Kamikakushi - Purwantini, Ni Kadek; Suartini, Ni Nengah; Adnyani, Kadek Eva Krishna (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 4 No 1 (2022), 2022)
This study aims to describe the equivalence of translating Japanese cultural terms into Indonesian in the anime Sen to Chihiro no Kamikakushi and the translation procedures applied in translating SL (source language) into TL (target language). This research is a qualitative descriptive study using data cards. The theory used is the category of cultural terms by Newmark (1988), the theory of equivalence by Nida and Taber (1974), and the theory of translation procedures by Newmark (1988). There are 38 data which are Japanese cultural terms and its translations in Indonesian. The results showed that 30 data reached equivalence and 8 data did not reach equivalence. Then, there are 7 translation procedures applied, including cultural equivalent, synonym, neutralization, additional explanation, modulation, transposition, and reduction and expansion. Cultural equivalence and synonyms are the most frequently applied procedures.